Investigating the genetic and epigenetic basis of big biological questions with the parthenogenetic marbled crayfish: a review and perspectives - Vogt, Günter (Journal of biosciences, 2018)
In the last 15 years, considerable attempts have been undertaken to develop the obligately parthenogenetic marbled crayfish Procambarus virginalis as a new model in biology. Its main advantage is the production of large numbers of offspring that are genetically identical to the mother, making this crustacean particularly suitable for research in epigenetics. Now, a draft genome, transcriptome and genome-wide methylome are available opening new windows for research. In this article, I summarize the biological advantages and genomic and epigenetic features of marbled crayfish and, based on first promising data, discuss what this new model could contribute to answering of “big” biological questions. Genome mining is expected to reveal new insights into the genetic specificities of decapod crustaceans, the genetic basis of arthropod reproduction, moulting and immunity, and more general topics such as the genetic underpinning of adaptation to fresh water, omnivory, biomineralization, sexual system change, behavioural variation, clonal genome evolution, and resistance to cancer. Epigenetic investigations with the marbled crayfish can help clarifying the role of epigenetic mechanisms in gene regulation, tissue specification, adult stem cell regulation, cell ageing, organ regeneration and disease susceptibility. Marbled crayfish is further suitable to elucidate the relationship between genetic and epigenetic variation, the transgenerational inheritance of epigenetic signatures and the contribution of epigenetic phenotype variation to the establishment of social hierarchies, environmental adaptation and speciation. These issues can be tackled by experiments with highly standardized laboratory lineages, comparison of differently adapted wild populations and the generation of genetically and epigenetically edited strains.
Gesehen am 27.03.2019